Ultreya: early adventures in alchemy - Engelen, Christine M., author; Doe, Sue, advisor; Candelaria Fletcher, Harrison, committee member; Denning, Scott, committee member (Colorado State University. Libraries, 2025)
Ultreya: Early Adventures in Alchemy is a collection of eleven personal essays written during my time in the CSU MFA in Creative Nonfiction program, between 2013 and 2025.The first four essays are excerpts from my writings on walking the French Route of the pilgrimage known as the Camino de Santiago, in July and August of 2008, when I was thirty years old. Like many young adults of that age, I was beginning to understand the fact of emotional baggage, and hoped that five weeks on the Camino Francés could teach me the secret of laying all that baggage down, and in the process, fix all that was wrong with me. Unsurprisingly, I remain to this day a highly imperfect creature. The second set of essays center around a sudden and unexpected diagnosis that I received shortly after I turned forty. That path contained easily as many mountains, pitfalls, and breakdowns as any long-distance pilgrimage, and ultimately offered just as many opportunities for alchemy: chances to transform hardship into something of value, something I could bear to carry with me for as long as my road might stretch into the future. A final two essays provide a look back on the path of my life from the fall of 2023, after I completed a second Camino, this time the Caminho Português, at the age of forty-five. I hope you find something of value in the pages that follow. Ultreya. Onward.
Keywords: camino; hiking; Santiago; diagnosis; alchemy; HIV+